Growth- and development characteristics of elite female age group swimmers - Barzdukas, A.; Spry, S.; Cappaert, J. M.; Troup, J. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
There is a strong relationship between physiological development, performance, and general growth and maturation during adolescence. Thus the purpose of this study was to examine skinfold thicknesses, stature, weight, Tanner development scores, hand-wrist radiographs, age of menarche, and Androgeny index (3 x biacromal breadth - bicristal breadth) in elite female age group swimmers. Subjects were divided into three groups based on age and performance level. Group I (n = 49, age= 160.40 ± 2.93), Group II (n = 28, age= 184.36 ± 3.96), and Group III (n = 24, age= 196.43 ± 3.95 years) varied significantly in terms of all anthropometric factors, except height and sum of skinfold, and performance times. In summary, (1) the group as a whole, had biological ages which exceeded the mean chronological ages by approximately 7 months. The older girls were, as expected, more physically mature - heavier, leaner with higher androgeny indices.